Effect of shoulder diameter to pin diameter ratio on microstructure and mechanical properties of dissimilar friction stir welded AA2024-T6 and AA7075-T6 aluminum alloy joints. Issue 9 (December 2016) - Saravanan, V.; Rajakumar, S.; Banerjee, Nilotpal; Amuthakkannan, R.
Abstract Friction stir welding (FSW) is a solid-state joining process that uses the frictional heat generated by the rotating tool to soften the metals to form the joint. It is an effective technique for joining dissimilar aluminum alloys and finds its application in various fields such as aerospace and automotive industries. The various FSW parameters play a vital role in determining the quality of the welded joint. The parameters included in the study are tool rotational speed, welding speed, axial load, and shoulder diameter to pin diameter ratio. This paper mainly focuses on studying the effect of shoulder diameter to pin diameter ratio (D /d ratio) on the microstructure and mechanical properties of the dissimilar AA2024-T6 and AA7075-T6 aluminum alloy joints. The weld quality characteristics like macrostructure, microstructure, microhardness, and tensile properties of the joints are analyzed and presented for five differentD /d ratios. The fractography images using scanning electron microscope (SEM) were presented for the joints with high and low strength. It is observed from the result that the joint fabricated usingD /d ratio of 3 exhibits the better mechanical properties when compared to other joints.